The Rosenblatt coefficient of dependence for m–dependent random sequences with applications to the ASCLT - Giuliano, R. (Інститут математики НАН України, 2008)
We prove a new bound for the Rosenblatt coefficient of the normalized partial sums of a sequence of m-dependent random variables; this bound is used to prove a general result, from which the Almost Sure Central Limit Theorem can be deduced.